The Phenomenon of Social Deconditioning Due to Digital Transformation: A Behavioral Neurobiology Analysis and Evidence-Based Recovery Strategies - Cicih Laelah; Rifqi Rifqi (Penerbit Hellow Pustaka, 2026)
The proliferation of digital technology and increasing online media consumption have fundamentally transformed human social interaction patterns. This study aims to analyze the phenomenon of social deconditioning—the weakening of face-to-face social stamina resulting from reduced exposure to embodied human interaction—and to formulate evidence-based recovery strategies. A systematic literature review was conducted on sources from social neurobiology, communication psychology, behavioral epidemiology, and public health science published between 2012 and 2024. Findings reveal: (1) face-to-face interaction activates neurological and hormonal systems that cannot be fully replicated by digital communication; (2) declining proportions of in-person interaction in daily life produce adaptive behavioral changes including functional social anxiety, difficulty sustaining conversational attention, and post-social fatigue; (3) this phenomenon represents an adaptive response rather than a personality disorder and is reversible; and (4) gradual recovery strategies based on incremental social exposure are effective in rebuilding social stamina. This study contributes to understanding the impact of digital transformation on population social health and offers an intervention framework applicable at both individual and community levels.